Toronto sprawls : a history - Solomon, Lawrence, 1948- (University of Toronto Centre for Public Management monograph series., 2007)
"Toronto Sprawls makes a convincing case that urban sprawl in Toronto was caused not by market forces, but rather by policies and programs designed to disperse Toronto's urban population."--Jacket